2013
DOI: 10.1534/g3.113.008417
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Genome-Wide Association Signals for Loss-of-Function Phenotypes in Sorghum Flavonoid Pigmentation Traits

Abstract: Genome-wide association studies are a powerful method to dissect the genetic basis of traits, although in practice the effects of complex genetic architecture and population structure remain poorly understood. To compare mapping strategies we dissected the genetic control of flavonoid pigmentation traits in the cereal grass sorghum by using high-resolution genotyping-by-sequencing single-nucleotide polymorphism markers. Studying the grain tannin trait, we find that general linear models (GLMs) are not able to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 53 publications
(94 reference statements)
3
75
0
Order By: Relevance
“…Dw2 has been mapped to chromosome 6 (Feltus et al, 2006;Zou et al, 2012;Nagaraja Reddy et al, 2013), and its effect on plant height is frequently detected in GWAS as a large genomic region encompassing almost the entire chromosome 6. This particular result is the consequence of the genetically converted sorghum accessions included in diversity panels such as the one investigated here (Klein et al, 2008;Morris et al, 2013;Zhang et al, 2015). Several linkage disequilibrium and linkage mapping studies also confirmed the location, importance, and effects of these two regions on chromosomes 6 and 9 on plant height (Upadhyaya et al, 2012;Zou et al, 2012;Morris et al, 2013, Nagaraja Reddy et al, 2013Zhang et al, 2015;Zhao et al, 2016).…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Dw2 has been mapped to chromosome 6 (Feltus et al, 2006;Zou et al, 2012;Nagaraja Reddy et al, 2013), and its effect on plant height is frequently detected in GWAS as a large genomic region encompassing almost the entire chromosome 6. This particular result is the consequence of the genetically converted sorghum accessions included in diversity panels such as the one investigated here (Klein et al, 2008;Morris et al, 2013;Zhang et al, 2015). Several linkage disequilibrium and linkage mapping studies also confirmed the location, importance, and effects of these two regions on chromosomes 6 and 9 on plant height (Upadhyaya et al, 2012;Zou et al, 2012;Morris et al, 2013, Nagaraja Reddy et al, 2013Zhang et al, 2015;Zhao et al, 2016).…”
Section: Discussionsupporting
confidence: 61%
“…This particular result is the consequence of the genetically converted sorghum accessions included in diversity panels such as the one investigated here (Klein et al, 2008;Morris et al, 2013;Zhang et al, 2015). Several linkage disequilibrium and linkage mapping studies also confirmed the location, importance, and effects of these two regions on chromosomes 6 and 9 on plant height (Upadhyaya et al, 2012;Zou et al, 2012;Morris et al, 2013, Nagaraja Reddy et al, 2013Zhang et al, 2015;Zhao et al, 2016). In spite of the similar performance and efficiency of both algorithms to estimate the actual morphological trait, Auto-PHe has the advantage of being an automatic processing pipeline with reduced run time and concomitant cost.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Since this gene has been mapped in the SAP (Morris et al 2013b), pericarp pigmentation was used as a control in this study to validate the genetic data. As expected, all of the models in GAPIT (GLM, MLM, and CMLM to control for population structure and kinship) identified a single region within the transcript of the Y1 locus ( Sobic.001G397900 ) that was strongly associated with seed color in the BAP (Figure 3).…”
Section: Resultsmentioning
confidence: 99%